(untitled) (Latakia University Journal -Biological Sciences Series, 2013)
The aim of this study is to evaluate the role of Bauhinia variegate, Bouganivillea glabra, Ligustrum vulgare and Ficus brnjamina as bioaccumulators for Nickel. The concentration of Nickel in the studied plant leaves, bark, wood and soils in Al-Forsan Garden (Lattakia City) was determined. The results showed that the Nickel concentration in the Ficus brnjamina leaves and bark was significantly high (11.04 and 12.37 ppm) respectively compared to other studied plants, whereas the nickel concentration was approximately the same in the other studied parts, and approximately the same as its natural concentration in plants. Our results also showed that the nickel concentration in the studied soil did not exceed the international norms of children gardens (about 57ppm), but it was very low regarding the park soils. The relationship between the nickel concentration in Ficus brnjamina wood and Bouganivillea glabra bark was the most significant.